1995
DOI: 10.1002/j.2050-0416.1995.tb00871.x
|View full text |Cite
|
Sign up to set email alerts
|

THE BREWING POTENTIAL OF “ACHA” (DIGITARIA EXILIS) MALT COMPARED WITH PEARL MILLET (PENNISETUM TYPHOIDES) MALTS AND SORGHUM (SORGHUM BICOLOR) MALTS

Abstract: The malting and brewing characteristics of millets (Pennisetum typhoides and Digitarla exflia) and sorghum (Sorghum bicolor) were compared. Diastase, a-amylase, amyloglucosidase and proteases increased with malting time and the increase was associated with the modification. Development of hydrolytic enzymes was significantly higher in pearl millet and Digitaria exilis ("acha") than in sorghum at P 2 0.01. The major starch degrading enzyme in the three varieties of pearl millet (SE composite, SE.13 and SE 2124)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 12 publications
2
12
2
Order By: Relevance
“…These findings are in agreement with those of other authors working with sorghum 12,13,14,15,17,18,20,22 and millets 13,14,20,26 . Recently, Muoria and Bechtel 13 suggested that a germination temperature > 22°C would be more desirable for sorghum and pearl millet, than for barley, in order to obtain higher values of α-amylase.…”
Section: ! â â â Fqwtp7hâqbâvdaâepuvevwvaâqbâ8tayepcâsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in agreement with those of other authors working with sorghum 12,13,14,15,17,18,20,22 and millets 13,14,20,26 . Recently, Muoria and Bechtel 13 suggested that a germination temperature > 22°C would be more desirable for sorghum and pearl millet, than for barley, in order to obtain higher values of α-amylase.…”
Section: ! â â â Fqwtp7hâqbâvdaâepuvevwvaâqbâ8tayepcâsupporting
confidence: 93%
“…The limited work on millet malting has been mainly on finger millet 1,8,9,10,14,24,26 with less being done on pearl millet. 6,11,13,20,25 The aim of this investigation was to determine optimum pearl millet malting conditions.…”
Section: -2863(9'8-32mentioning
confidence: 99%
“…Extract, as with DP, FAN and beta-amylase activity, increased with germination time. This is in agreement with findings for sorghum 6,15,20 , finger millet 17 and pearl millet 20 . The increase in hot water extract with germination time is an indication of the progress of modification (breakdown of the endosperm reserves, predominantly by amylase and protease activity) of the malt during germination 3 .…”
Section: Extractsupporting
confidence: 93%
“…The low-starch gelatinisation temperature (Jideani et al 1996) and high-beta-amylase activity (Nzelibe and Nwasike 1995;Nzelibe et al 2000) shows the brewing potential of acha and iburu in partial substitution of barley malt. Values are mean ± standard deviation; Means with different superscript within the same column differ significantly (p<0.05) using Duncan multiple range test Agu et al (2007) Constraints and opportunities for commercialisation…”
Section: Other Food Uses Of Acha and Iburumentioning
confidence: 97%